Design and evaluation of rear axle side slip stability control for passenger cars: simulations and experimental verification of interventions in oversteer situations - Östh, Jonas; Billmark, Johan (My University, 2007)
Vehicle stability control has had a remarkable effect on the active safety of passenger cars. Therefore further development of vehicle stability control systems is an ongoing activity in the automotive industry. The objective of this project was to develop a rear axle side slip angle controller to improve the stability control for passenger cars in oversteer situations. In these situations, the vehicle has a significant lateral velocity and can even start skidding sideways. This is a potentially dangerous condition because the vehicle is then also insensitive to steering wheel inputs from the driver. Interventions from the stability control system can prevent this condition and increase the active safety of passenger cars. The developed controller is implemented in a simulation environment consisting of the vehicle dynamics simulation tool Vedyna available in Matlab/Simulink. To enable evaluation in vehicle tests the controller was developed as an extension to existing production like stability control functions. For the evaluation in both simulations and vehicle tests two relevant test cases were chosen. The first test case was the J-turn maneuver, resembling a highway exit where the vehicle can experience oversteer as the result of a load transfer when decelerating. The second test case was an evasive maneuver in the form of a double lane change. The latter test case is used to verify that the vehicle maneuverability was not impaired by the developed controller. Using rapid control prototyping tools the tests were also carried out in a vehicle on the test track to verify the previous results from the simulations. The results from simulations and experiments show that adding rear axle side slip angle control to regular stability control functions can improve the stability control in oversteer situations. The developed controller helps the driver to maintain control of the vehicle even if the driver reacts late in a maneuver like the J-turn. Furthermore, it was shown that the performance in evasive maneuvers can be enhanced rather than impaired by the developed controller. For the double lane change maneuver studied the entrance speed was increased by up to 2 km/h. Lastly, it should be noted that the developed function is depending on a reliable estimation of the rear axle side slip angle, why further work is needed before the functionality can be industrialized.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering